2021
DOI: 10.1007/s00167-021-06597-6
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral coracohumeral distance discrepancy is associated with subscapularis tear in rotator cuff rupture patients

Abstract: Purpose To describe the bilateral coracohumeral morphological discrepancy in rotator cuf rupture patients with and without subscapularis (SSC) involvement and to investigate its association with SSC tears. Methods Two hundred and thirteen consecutive patients who were scheduled to have arthroscopic rotator cuf repair were prospectively enrolled in the current study. Patients with acute traumatic rotator cuf rupture, glenohumeral osteoarthritis, bilateral rotator cuf rupture, recurrent shoulder instability, sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…But in clinical practice, we found that it was difficult to select an ideal measurement plane on MRI according to the defined method, and the clinical practicability was poor. Based on previous literature reports, clinical importance, and practicality, three coracoid morphological parameters including CHD, CO, and CHI were considered potential candidates for SSC tendon tears [ 24 , 29 , 39 ]. To further evaluate the relationship between coracoid morphology and SSC tendon tears, we measured CHD (axial plane), CHD (oblique sagittal plane), CHI (axial plane), and CO (axial plane) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…But in clinical practice, we found that it was difficult to select an ideal measurement plane on MRI according to the defined method, and the clinical practicability was poor. Based on previous literature reports, clinical importance, and practicality, three coracoid morphological parameters including CHD, CO, and CHI were considered potential candidates for SSC tendon tears [ 24 , 29 , 39 ]. To further evaluate the relationship between coracoid morphology and SSC tendon tears, we measured CHD (axial plane), CHD (oblique sagittal plane), CHI (axial plane), and CO (axial plane) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Leite et al emphasized that narrowing the coracohumeral distance and an increase in the coracoid overlap distance are good indicators of SS ruptures [8]. Likewise, Zhu et al in a prospective study comparing bilateral shoulders, stated that coraco-humeral distance was the best predictor of SS ruptures (P<0.0001) [28]. In the present study, coraco-humeral distance decrease and coracoid overlap increase were found to be statistically significant indicators, similar to these studies (both P<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Leite et al showed that the CO had a strong predictive value for SSC tears, and when the CO value was 16.6 mm, the sensitivity and specificity for the prediction of SSC muscle tears reached the optimal value [13]. However, Zhu et al found that a CO value of 10 mm had the most appropriate sensitivity and specificity for the prediction of SSC tears, and the predictive value was higher than that of CHD [9]. Cetinkaya et al identified the CO as the most valuable predictor of SSC tears [23].…”
Section: Discussionmentioning
confidence: 99%
“…There were 1 092 patients included in the four studies [9,15,19,25]; the experimental group had 532 patients, and the control group had 560 patients. There was no heterogeneity (I 2 = 0 %, P = 0.77).…”
Section: Dominant Armmentioning
confidence: 99%